Marketing Strategy For Flower Board Rental Business At Galeri Asiah Florist Manna, South Bengkulu Regency - Riski, Muhammad Ikmal; Wijaya , Ermy; Zoniarti , Zoniarti (Universitas Dehasen Bengkulu, 2024)
Flower bouquet boards are Micro, Small and Medium Enterprises (MSMEs) in the world of services. MSMEs are one of the key factors in driving economic growth in Indonesia. Asiah Florist Gallery in Manna, South Bengkulu, which is engaged in a service company, namely a flower board business that rents bouquets. This type of research uses quantitative research. The analysis method in this study uses SWOT analysis and hypothesis testing using the t test. The number of samples studied was 55 people consisting of 50 randomly selected consumers as well as 4 employees and 1 leader at Asiah Florist Manna. The result of the summation of the strengths possessed is 27.05 while the weaknesses are 18.95, then the internal quadrant of factors is 27.05 - 18.95 = 8.11, meaning the ability of marketing at Asiah Florist Manna, South Bengkulu Regency in utilizing the strengths and minimizing the weaknesses contained in the internal. The opportunities that the strategy has are 18.49 and the threat is 13.84. Then the external quadrant of factors, namely 18.49 - 13.84 = 4.65, means that the high ability of marketing at Asiah Florist Manna, South Bengkulu Regency to take advantage of opportunities and overcome threats faced by Asiah Florist Manna City, South Bengkulu in business development.